A224 BLOOD TRANSFUSION IN UPPER GASTROINTESTINAL BLEEDING: EVALUATING PHYSICIAN PRACTICES IN THE EMERGENCY DEPARTMENT. (15th March 2019) - Stach, J; Sandha, S; Bullard, M; Halloran, B; Blain, H; Sandha, G S; Grigat, D; Lang, E; Veldhuyzen van Zanten, S
Abstract: Background: Acute upper gastrointestinal bleeding (UGIB) is a common presentation to emergency departments (ED). Of these patients, 35–45% receive a blood transfusion. Guidelines for blood transfusion in stable UGIB have been well established, and recommend a hemoglobin (Hb) level of 70 g/L as the transfusion target. There is no consensus on a transfusion threshold for unstable UGIB. There is limited data regarding physician practices in the ED. Aims: i) To determine the appropriateness of blood transfusions in UGIB in a tertiary care hospital ED. ii) To determine if the current guideline recommendation for a transfusion target of a Hb of 70 g/L is appropriate in unstable UGIB. Methods: We retrospectively reviewed patients presenting with UGIB to the University of Alberta Hospital ED in 2016. The Emergency Department Information System (EDIS) and TANDEM databases were queried for ICD-10 codes and the EDIS complaints of vomiting blood or blood in stool/melena. These patients were screened for blood transfusions, and only those who received a blood transfusion are reported here. Data were obtained from the patient records. Chart derived data were verified with records obtained from the blood bank. For each patient, the history, vitals, Glasgow Blatchford Score (GBS), relevant labs, and record of blood transfusions were collected and organized into a case summary. Each patient summary was presented individually to a panel of three expert clinicians (2 Gastroenterology, 1 Emergency Medicine), who then decided on the appropriateness of each blood transfusion by consensus. Results: 43.5% (87/200) of patients presenting with UGIB received a blood transfusion. Of these, 80.4% (70/87) were judged to be appropriate. Details of the transfusion data are shown in Table 1. Of all transfusions received by patients with a Hb >70 g/L, 56.4% (22/39) were considered appropriate. Conclusions: 80% of blood transfusions for UGIB at our institution were considered appropriate by a panel of expert clinicians. All transfusions under the recommended guideline of 70 g/L were considered appropriate. In addition, the majority of transfusions above a Hb of 70 g/L were considered appropriate. Further studies evaluating the feasibility of current guideline recommendations in an ED setting are required. Educational interventions should be created to reduce inappropriate blood transfusions above a Hb of 70 g/L. Funding Agencies: Emergency Strategic Clinical Network (ESCN), Alberta Health Services (AHS)